Stellenwert der Biopsie in der Diagnostik chronischer Wunden – ein Positionspapier der Initiative Chronische Wunden (ICW) e. V. - Erfurt-Berge, Cornelia; Bültemann, A.; Gerber, V.; Motzkus, M.; Rembe, J. D.; Dissemond, J. (Die Dermatologie, 2023)
Diagnostic assessment of chronic wounds is essential for the initiation of causal therapeutic treatment. For diagnostic classification of the wound genesis, it may be necessary to take a tissue sample for histological and/or microbiological processing. If there is clinical suspicion of a specific cause of the wound such as a neoplasm, an inflammatory dermatosis or a pathogen-induced wound, a tissue sample for further diagnosis is required immediately. If the ulceration does not respond sufficiently to adequate causal therapy, a tissue sample for further evaluation is recommended after 12 weeks. The choice of the correct sampling technique, further storage, transport and processing are just as decisive for a reliable result as the specific question for the diagnostic laboratory.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Differential diagnosis; Histology; Leg ulcer; Microbiology; Tissue sample